Oracle 10g developing media rich applications - Guros, Larry; Dunckley, Lynne (Burlington, MA : Elsevier Digital Press, 2007)
Oracle 10g Developing Media Rich Applications is focused squarely on database administrators and programmers as the foundation of multimedia database applications. With the release of Oracle8 Database in 1997, Oracle became the first commercial database with integrated multimedia technology for application developers. Since that time, Oracle has enhanced and extended these features to include native support for image, audio, video and streaming media storage; indexing, retrieval and processing in the Oracle Database, Application Server; and development tools. Databases are not only words and numbers for accountants, but they also should utilize a full range of media to satisfy customer needs, from race car engineers, to manufacturing processes to security. The full range of audio, video and integration of media into databases is mission critical to these applications. This book details the most recent features in Oracles multimedia technology including those of the Oracle10gR2 Database and the Oracle9i Application Server. The technology covered includes: object relational media storage and services within the database, middle tier application development interfaces, wireless delivery mechanisms, and Java-based tools. * Gives broad coverage to integration of multimedia features such as audio and instrumentation video, from race cars to analyze performance, to voice and picture recognition for security data bases. As well as full multimedia for presentations * Includes field tested examples in enterprise environments * Provides coverage in a thorough and clear fashion developed in a London University Professional Course.
1. Introduction: -- Oracle Database and Application Server 10g; What they Mean For Business Goals for this book -- Market -- -- Drivers: web, wireless, digital imagery -- -- Segments: banking, security, defence, real estate, retail -- 2. Multimedia Explained -- Analog Media -- Digital Media -- Digital Media Formats -- -- file formats -- -- compression schemes -- -- pixel formats -- -- image formats -- -- audio formats -- -- video formats -- 3. How does Oracle10g support image, audio and video content? -- Media Packaging -- -- blobs -- -- objects -- -- structure -- -- attributes -- -- methods -- -- initialization -- Media in relational tables -- 4. Getting Ready: What you need to know before you media-enhance your application. -- Planning The Development Process. -- Gathering Requirements. -- <Schema Definition> -- Architecture. -- Server -- -- interMedia -- Middle Tier Architecture -- -- Oracle Application Server Wireless -- -- media adaptation -- -- streaming video services -- -- Tools -- -- Portal -- -- Jdev -- -- Wireless -- Development Planning. -- Construction Planning. -- Summary. -- 5. Building the database -- Database Administrator Role -- Installation & Upgrades -- -- installation & configuration -- -- installation check -- -- verify installation -- -- upgrade -- -- downgrade -- -- deinstall -- 6. Protecting your data -- Performing Essential intermediaTasks -- Optimizing the Configuration of the Database Engine. -- Performance tuning -- Tools to Measure Performance -- 7. Where and how to use intermedia -- Database Programmer Role -- Management Utility -Enterprise Manager -- 8. Building a simple application -- Application Optimization. -- Looking Behind the Scenes. -- -- bulk loading -- -- indexing -- Object interfaces -- Relational interfaces -- 9. Creating image audio, and video objects with intermedia Exploring the Benefits of Using Objects. -- Java Media Classes -- -Java Introduction -- -Ord Image Class -- -Ord Audio Class -- -Ord Video Class -- -Ord Doc Class -- -Common Object Methods -- -- interMedia classes for servlets and JSPs -- Reviewing Objects, Properties, and Methods. -- Summary. -- 10. Java Application Development -- -JDBC Connection -- -Java Servlet Classes -- -Java Servlet Access -- -Java HTTP Download To Browser -- -Java HTTP Upload from Browser -- <JSP Tag Library> -- 11. Advanced Queries -- Content Based Retrieval. -- Problems & challenges -- Standards -- Image content based retrieval -- -- image signature -- -- specialized index -- -- image matching -- -- domains of utility -- Speech content based retrieval -- -- 3rd party speech recognition -- -- speech index -- -- text based speech mining -- 12. Java Development Tools -- -- JDeveloper & BC4J -- -- Java Advanced Imaging -- -- Java Media Framework -- Java Delivery JSPs -- JSP Tag Library -- 13. Using PL/SQL for intermedia applications -- Server Side Sql -- Web Sql -- Code Wizard -- Understanding Queries using Intermedia objects -- Mastering multimedia Queries. -- Optimizing Queries. Summary. -- 14. Multimedia Database Middleware -- Coping with multimedia data on networks -- Streaming Media -- Oracle Application Server 10i -- Media adaptation services -- Wireless media delivery -- Database Security and Reliability -- 15. XML and SMIL: Something to Smile About -- Interoperability -- ASP VB -- Portal forms and reports -- 16. Understanding the Big Picture. -- Demonstration Application -- 15 Pages -- Photo Album -- -- Java -- -- JSP -- -- PL/SQL -- Putting It All Together. -- Tips and Techniques. -- Appendix A: Installing Oracle Intermedia. -- Appendix B: About PL/SQL Versions. intermedia Resources for PL/SQL Developers -- Appendix C: CD Contents. -- Index.
Includes index.
Keywords: Relational databases; Oracle (Computer file); Electronic books